2017
DOI: 10.1016/j.ebiom.2017.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Causes Circadian Dysfunction: A Potential Risk Factor for Cardiovascular Disease

Abstract: Hypercholesterolemia is a well-known risk factor for a wide range of diseases in developed countries. Here, we report that mice lacking functional LDLR (low density lipoprotein receptor), an animal model of human familial hypercholesterolemia, show circadian abnormalities. In free running behavioral experiments in constant darkness, these mice showed a prolonged active phase and distinctly bimodal rhythms. Even when the circadian rhythms were entrained by light and dark cycles, these mice showed a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…28 per2 has been the focus of studies regarding cardiovascular diseases. 29 In this study, we demonstrated a circadian pattern of per2 protein expression and the LC3-II/I ratio in the mouse heart. Previous studies had found that there was a circadian rhythmicity of MI incidence, infarct size, and clinical outcomes in STEMI.…”
Section: Discussionmentioning
confidence: 49%
“…28 per2 has been the focus of studies regarding cardiovascular diseases. 29 In this study, we demonstrated a circadian pattern of per2 protein expression and the LC3-II/I ratio in the mouse heart. Previous studies had found that there was a circadian rhythmicity of MI incidence, infarct size, and clinical outcomes in STEMI.…”
Section: Discussionmentioning
confidence: 49%
“…CCGs are involved in various physiological activities, including cell proliferation, apoptosis, cell cycling, metabolism, endocrine signaling and immunity (4)(5)(6)(7)(8). As a result, abnormal expression of clock genes can lead to a variety of diseases, including endocrine disorders, cardiovascular diseases and tumors (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study by Mergeani et al (2015) demonstrated that increased total and low density lipoprotein (LDL) cholesterol are significantly associated with a disrupted circadian rhythm of BP [ 34 ]. Interestingly, mice lacking functional LDL-receptor, an animal model of human familial hypercholesterolemia, exhibit abnormal circadian behavior [ 35 ]. Additionally, the introduction of a genetic mutation in the Per 2 gene resulted in mice with a significant enlargement of artery plaque area and increased levels of the inflammatory cytokine interleukin 6 (IL-6).…”
Section: The Circadian Timing System and Diurnal Variation Of Bp Imentioning
confidence: 99%